[18F]Flutemetamol PET imaging and cortical biopsy histopathology for fibrillar amyloid β detection in living subjects with normal pressure hydrocephalus: pooled analysis of four studies - Rinne, Juha O.; Wong, Dean F.; Wolk, David A.; Leinonen, Ville; Arnold, Steven E.; Buckley, Chris; Smith, Adrian; McLain, Richard; Sherwin, Paul F.; Farrar, Gill; Kailajärvi, Marita; Grachev, Igor D. (Acta neuropathologica, 2012)
Molecular imaging techniques developed to ‘visualize’ amyloid in vivo represent a major achievement in Alzheimer’s disease (AD) research. This pooled analysis of four studies determined the level of association between uptake of the fibrillar amyloid β positron emission tomography (PET) imaging agent [ 18 F]flutemetamol (Pittsburgh Compound B analog with a 5.5 times longer half-life to enable it to be used in the clinical setting) and neuritic plaques and fibrillar amyloid β measured by pathologic staining of cortical region biopsy samples. Fifty-two patients with suspected normal pressure hydrocephalus underwent prospective ( n = 30) or retrospective ( n = 22) [ 18 F]flutemetamol PET imaging for detection of cerebral cortical fibrillar amyloid β and cortical brain biopsy during intracranial pressure measurement or ventriculo-peritoneal shunting. [ 18 F]Flutemetamol uptake was quantified using standardized uptake value ratio (SUVR) with cerebellar cortex as the reference region. Tissue fibrillar amyloid β was evaluated using immunohistochemical monoclonal antibody 4G8 and histochemical agents Thioflavin S and Bielschowsky silver stain, and an overall pathology result based on all available immunohistochemical and histochemical results. Biopsy site and contralateral [ 18 F]flutemetamol SUVRs were significantly associated with neuritic plaque burden assessed with Bielschowsky silver stain ( r spearman’s = 0.61, p = 0.0001 for both), as was the composite SUVR with biopsy pathology ( r spearman’s = 0.74, p < 0.0001). SUVR and immunohistochemical results with 4G8 for detecting fibrillar amyloid β were similar. Blinded image evaluation showed strong agreement between readers ( κ = 0.86). Overall sensitivity and specificity by majority read were 93 and 100 %. Noninvasive in vivo [ 18 F]flutemetamol PET imaging demonstrates strong concordance with histopathology for brain fibrillar amyloid β, supporting its promise as a tool to assist physicians with earlier detection of the disease process and making diagnostic decisions about concomitant AD and other diseases associated with brain amyloidosis.